Toll Like Receptor 4 (Tlr4) And p65 Nuclear Factor Kappa B (Nf-Kb) Expression In Monocyte Cell Of Children With Steroid Resistant Nephrotic Syndrome - Tikto Wahyono; Krisni Subandiyah; Loeki Enggar Fitri; Agustina Tri Endharti (Journal of Tropical Life Science, 2014)
This study aimed to prove the difference of TLR4 and subunit p65NF-kB expression between children with steroid-sensitive nephrotic syndrome (SSNS) and those with steroid-resistant nephrotic syndrome (SRNS) and to find out the correlation between expression of TLR4 and p65NF-kB on children with SRNS. Twenty three patients of idiopathic nephrotic syndrome patients (INS) were enrolled in this study and classified into two groupsâ€”those with SSNS (11 patients) and SRNS (12 patients). Peripheral Blood Mononuclear Cells (PBMC) isolation was performed, taken from 5 ml patients blood samples, followed by monocyte isolation of PMBC using monocyte culture. Examination of TLR4 and p65 NF-kB expression from monocyte's cells culture was performed using flow cytometry. All data were processed using Statistical Package for the Social Sciences (SPSS 15) for Windows. From 11 patients that were classified into SSNS group, 81.8% having good nutritional status and 18.2% comprising undernourished status compared to 12 patients of the SRNS group, in which 6 accounting for 41.7% having good nutritional status, 50% having undernourished status and 8.3% having malnourishment status. The average age is 7.59 ± 3.52 and six years old is the highest age studied. Based on normality tests using Shapiro-Wilk, variables of TLR4 have p value of 0.620 and p65 NF-kB have p value of 0.027, showing that the data of TLR4 was distributed normally but p65 NF-kB data was not distributed normally. The test on TLR4 data variation using Levene Test showed its significance value of p was 0.318, meaning that the data was homogeneous. Using unpaired t-test, the differences of TLR4 expression between SSNS and SRNS was significant (p=0.012), while using Mann-Whitney test, the differences of p65 NF-kB expression between SSNS and SRNS showed an insignificant correlation (p=0.880). Pearson correlation test between the expression of TLR4 and p65 NF-kB showed no significant correlation (p=0.472), while Spearman correlation test to see the relationship between expression of TLR4 and SRNS produced correlation value of 0.512 and its importance p value was 0.013 (p